Identification to oneself and to the others: Employees' perceptions after a merger - Ralf Bebenroth; Kai Oliver Thiele (University of Duisburg-Essen, Institute of East Asian Studies (IN-EAST), 2015)
This study sheds light on how employees identify with organizational change after a cross-border acquisition. Specifically, we tested how target and bidder employees identify against each other. We extend previous findings from the literature that both acquiring and target organizations continue to identify stronger with themselves than with the opposing side. However, self-identification for target employees shrinks down in contrast to bidder employees which remains rather stable. Also, bidder employees identify lower to targets than target employees to the bidder firm. We find that a higher self-identification leads to a higher identification towards the other group. Furthermore, there is some evidence that motivational cultural intelligence of employees and a higher contact intensity to the other side moderate the relationship to the other groups identification. Also, highly self-identified employees which are culturally more intelligent and with a higher contact intensity to the other group identify higher to the other group. Implications and future research directions are discussed.
Keywords: 330; M&A; employees' perceptions; organizational identification; motivational cultural intelligence; contact intensity